Low molecular weight polysialic acid prevents lipopolysaccharide‐induced inflammatory dopaminergic neurodegeneration in humanized SIGLEC11 transgenic mice. Issue 12 (18th August 2021) - Liao, Huan; Winkler, Jonas; Wißfeld, Jannis; Shahraz, Anahita; Klaus, Christine; Neumann, Harald
Abstract: Parkinson's disease is one of the most common neurodegenerative diseases in the elderly population, with a pathophysiology linked to neuroinflammation, complement activation, and oxidative damage. Soluble polysialic acid with an average degree of polymerization 20 (polySia avDP20) prevents inflammation and oxidative burst in human macrophages via sialic acid‐binding immunoglobulin like lectin‐11 (SIGLEC11) receptor and interferes with alternative complement activation. Here, we confirmed the anti‐inflammatory capacity of polySia avDP20 on cultured murine embryonic stem cell‐derived microglia and analyzed the effect of polySia avDP20 in a lipopolysaccharide‐triggered animal model of Parkinson's disease. We demonstrated a neuroprotective effect of intraperitoneally applied polySia avDP20 in humanized SIGLEC11 transgenic mice after repeated systemic challenge with lipopolysaccharide. Pathway enrichment analysis of the brain transcriptome on day 19 after disease initiation showed that intraperitoneal application of 10 μg/g body weight polySia avDP20 prevented excessive inflammation. In line with these data, polySia avDP20 attenuated the lipopolysaccharide‐triggered increase in mRNA levels of immune‐related genes ( Il1b, Cd14, Myd88, Fcer1g, Itgam, C4, Cybb, Iba1 and Cd68 ) and cell death‐related genes ( Casp8, Ripk1 and Ripk3 ) in the brains of SIGLEC11 transgenic mice on day 19, but not on day 5. Moreover, immunohistochemistry demonstrated that polySia avDP20 reduced the lipopolysaccharide‐induced increase in immunoreactivity of IBA1 and CD68 in the substantia nigra pars reticulata in SIGLEC11 transgenic and wild type mice on day 19. Furthermore, treatment with polySia avDP20 prevented the loss of dopaminergic neurons in the substantia nigra pars compacta induced by lipopolysaccharide challenge in both SIGLEC11 transgenic and wild type mice on day 19. Thus, our data demonstrate that polySia avDP20 ameliorates inflammatory dopaminergic neurodegeneration and therefore is a promising drug candidate to prevent Parkinson's disease‐related inflammation and neurodegeneration. Main Points: Liao et al. demonstrate that soluble polysialic acid, an anionic polymer of the cellular glycocalyx, ameliorates detrimental inflammatory dopaminergic neurodegeneration in a lipopolysaccharide‐triggered mouse model of Parkinson's disease.